Emergence Of Technology In Workforce Collaboration - Othman, Nur Dina (2005)
The study main focus is to find out whether there is any positive relationship between technology and collaboration, and technology and performance. Apart from that, the study also seeks to find out other determinants that influence technology implementation and usage satisfactions.